Optimizing a Synergistic Bacterial Consortium for the Bioremediation of Multi-Metal Contaminated Soils in Jimeta, Nigeria - Abubakar Isah Muhammad; Faisal Bello; Fidelis Fredrick Umaru; Adamu Magaji Bappa (Biology, Medicine, & Natural Product Chemistry, 2026)
Soil contamination with anthropogenic heavy metals presents a critical threat to ecosystem stability and public health, demanding the development of sustainable in-situ remediation technologies. This study engineered and optimized a synergistic bacterial consortium for bioaugmenting multi-metal-contaminated soil from an active scrap dump in Jimeta, Nigeria. We isolated and characterized indigenous, metal-resistant strains of Pseudomonas, Bacillus, and Staphylococcus, which exhibited minimum inhibitory concentrations for chromium and other metals that far exceeded in-situ soil levels, confirming exceptional intrinsic tolerance. A systematic multivariate optimization of key abiotic factors defined the consortium's operational window, identifying neutral pH (7.0) and a mesophilic temperature of 30°C as optimal for peak bioremediation efficiency. While individual bacterial species achieved moderate metal removal (21.6–28.6%), the designed tertiary consortium demonstrated markedly superior performance, attaining 62.8% removal, a synergistic enhancement of approximately 125% over the mean axenic culture output. This significant boost is attributed to complementary microbial mechanisms, including partitioned detoxification pathways, syntrophic cross-feeding, and collective production of metal-chelating siderophores. Notably, these optimized conditions align with the prevailing edaphic parameters of tropical soils in Northern Nigeria, underscoring the ecological coherence and practical field applicability of this approach. The findings robustly validate the principle of functional microbial synergy for remediating complex polymetallic contamination. Consequently, this work establishes a scientific and technical foundation for transitioning consortium-based bioremediation from laboratory proof-of-concept to a predictable, scalable field technology. It advocates for a paradigm shift from conventional, reactive cleanup methods toward proactive, ecological engineering strategies that mitigate metal bioavailability, protect agro-ecosystems, and interrupt a key environmental determinant of chronic disease.